Self-Compassion And Mindfulness-Based Psychological First Aid Module: Strategies For Improving The Resilience Of Pioneer Whistleblowers Of The Children's Forum - Harum, Akhmad; Nurul, Annisa; Pandang, Abdullah (Educational Guidance and Counseling Development Journal, 2025)
Resilience is an individual's ability to survive, adapt and recover from stress. Psychological first aid is the initial psychological aid to help people who are suffering and need the support of others. Self-compassion is a kind attitude towards oneself when facing difficulties. Mindfulness is mindfulness of the present moment of life without being bound by a particular point of view. The module is a mentoring intervention medium that can help members of the Hasanuddin Tamalla'jua Children's Forum to increase resilience. The research objectives are to: 1) Knowing the needs of the module; 2) Know the prototype of the module; 3) Assess the validity of the module; 4) Assess the practicality of the module. The research method used is the Research and Development Analyze, Design, Development, Implementation, and Evaluation (ADDIE) model. Data analysis used descriptive qualitative and quantitative analysis with instruments in the form of questionnaires, interviews, and observations. The results showed that: 1) The resilience of Hasanuddin Tamlla'jua Children's Forum members is not optimal, with difficulties managing emotions, lack of confidence, and adapting; 2) The Psychological First Aid module prototype was designed to improve resilience with a combination of self-compassion and mindfulness, developed using Microsoft Word and Canva Pro; 3) The module is very valid, with 97.2% material validation and 98.6% media; 4) The module is very practical, with a score of 91.6% in the practitioner and small group tests, and is feasible to be tested at the Hasanuddin Tamlla'jua Children's Forum to improve the resilience of its members.